La viscosupplementazione nei pazienti emofilici - Falez, Francesco; La Cava, Filippo; Ciolli, Luigi; Ciompi, Alessandro (Lo Scalpello - Journal, 2019)
VISCOSUPPLEMENTATION IN HAEMOPHILIC PATIENTSWe evaluated the results obtained from the treatment of 88 intraarticular hyaluronic acid injections in haemophilicarthropathy according to the parameters of pain, function, health and radiographic evaluation. In 58 joints there wasan improvement in the conditions preceding the treatments, in 20 the joint disease was stabilised, in 10 the treatmentwas ineffective and 9 of these were subsequently operated. 36 patients repeated the cycle at a distance. No adverseeffects. Haemophilic arthropathy in its mild or moderate forms of joint damage can be effectively treated withviscosupplementation.